Advancement of New Values in Economy and Their Impacts on Tourism - KHARE, JASMIN (The journal of contemporary issues in business and government, 2021)
Nowadays, when "industrial society" has risen as an "information society" by encountering change with the impact of a rebellion like Business 4.0, the developments of numeral standards in the novel budget show a significant part. Digital communication systems, bitcoin and blockchain that change communications methods among manufacturers and customers will undoubtedly influence the change of the travel industries as in different businesses. The formation of the components of economic growth and the effects of digitalization makes research into the ties between business and innovation in the travel industry as important as in many other sectors. In this unique situation, a works study remained completed on the use of block chain innovations in the travel industry businesses so as to exhibit the financial approaches that can be created toward change in the travel industry, the place and their use in financial affairs of modern creative currency qualities in the travel industry. In this particular case, a literature review on the monetary approaches to the transition in the travel industry have been carried out., the spot of new industrial financial qualities in the travel industry economy and the use of block chain innovations in the travel industries.